A novel approach to monitoring the efficacy of anti-tumor treatments in animal models: combining functional MRI and texture analysis - Ming Meng; Huadan Xue; Jing Lei; Qin Wang; Jingjuan Liu; Yuan Li; Ting Sun; Haiyan Xu; Zhengyu Jin (BMC Cancer, 2018)
Abstract Background The aim of this study was to evaluate the early anti-tumor efficiency of different therapeutic agents with a combination of multi-b-value DWI, DCE-MRI and texture analysis. Methods Eighteen 4 T1 homograft tumor models were divided into control, paclitaxel monotherapy and paclitaxel and bevacizumab combination therapy groups (n = 6) that underwent multi-b-value DWI, DCE-MRI and texture analysis before and 15 days after treatment. Results After treatment, the tumors in the control group were significantly larger than those in the combination group (P = 0.018). In multi-b-value DWI, the ADCslow obviously increased in the combination group compared to that in the others (P < 0.01). The f increased in the control and paclitaxel groups, but the combination group showed a significant decrease versus the others (P < 0.02). Additionally, in DCE-MRI, the decreasing Ktrans showed an evident difference between the combination and control groups (P = 0.003) due to the latter’s increasing Ktrans. The intra-group comparisons of tumor texture in pre-, mid- and post-treatments showed that the entropy had all significantly increased in all groups (P < 0.01, SSF = 0–6), though the MPP, mean and SD increased only in the combination group (PMPP,mean,SD < 0.05, SSF = 4–6). Moreover, the inter-group comparisons revealed that the mean and MPP exhibited significant differences after treatment (Pmean,MPP  < 0.05, SSF = 0–3). Conclusion All these results suggest some strong correlations among DWI, DCE and texture analysis, which are beneficial for further study and clinical research.